Ultra-Rapid Real-Time RT-PCR Method for Detecting Middle East Respiratory Syndrome Coronavirus Using a Mobile PCR Device, PCR1100 - Shirato, Kazuya; Nao, Naganori; Matsuyama, Shutoku; Kageyama, Tsutomu (Japanese Journal of Infectious Diseases, 2020)
Middle East respiratory syndrome (MERS) coronavirus (MERS-CoV) is usually diagnosed through highly sensitive and specific genetic tests such as real-time reverse transcription polymerase chain reaction (RT-PCR). Currently, two real-time RT-PCR assays targeting the upE and ORF1a regions of the MERS-CoV genome are widely used, and these are the standard assays recommended by the World Health Organization (WHO). The MERS outbreaks to date suggest that rapid diagnosis and subsequent isolation of infected patients, particularly superspreaders, are critical for containment. However, conventional real-time RT-PCR assays require large laboratory instruments, and amplification takes approximately 2 h. These disadvantages limit rapid diagnosis. Here, an ultra-rapid real-time RT-PCR test was established comprising a multiplex assay for upE and ORF1a running on a mobile PCR1100 device. As few as five copies of the MERS-CoV RNA can be detected within 20 min using the standard WHO assays in the mobile PCR device, with the sensitivity and specificity being similar to those of a conventional real-time PCR instrument such as the LightCyler, thereby enabling timely intervention to control MERS-CoV infection.